Half U-slot loaded semicircular disk patch antenna for GSM mobile phone and optical communications - Ansari J.A.; Mishra A.; Vishvakarma B.R. (My University, 2025)
In the present paper, a dual frequency resonance antenna is achieved by introducing half U-shaped slot in semicircular disk. It is analysed by using circuit theory concept. The resonance frequency is found to be 1.50 GHz and 2.32 GHz, and the bandwidth of the proposed antenna for lower and upper resonance frequency is found to be 5.96% and 11.08% respectively. It is found that the resonance frequency depends inversely on the slot length and feed point, while it increases with increasing the slot width and coaxial probe feed radius. The frequency ratio is found to be 1.54. The theoretical results are compared with IE3D simulation as well as reported experimental results, and they are in good agreement.